2019
DOI: 10.1111/ctr.13691
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of fungal infections in pancreas transplant recipients in the absence of systemic antifungal prophylaxis

Abstract: Background: There is a lack of high-level evidence identifying meaningful outcomes and the place in therapy for systemic perioperative antifungal prophylaxis (ppx) in pancreas transplant recipients. As our program does not routinely utilize systemic perioperative antifungal ppx in pancreas transplant recipients, we assessed the incidence of post-transplant infectious complications. Methods: This was a single-center, retrospective cohort study of consecutive adult pancreas transplant recipients between 01/2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 17 publications
4
24
0
2
Order By: Relevance
“…The lack of antifungal prophylaxis did not affect the incidence of IC [76]. Similar to Bartoletti, in a recent singlecenter study, Shaik et al showed that enteric-drained pancreas transplant recipients who did not receive systemic antifungal prophylaxis had similar infectious complications, including an incidence of invasive candidiasis of 3.6%, which is similar to previously reported rates [75].…”
Section: Pancreassupporting
confidence: 74%
See 1 more Smart Citation
“…The lack of antifungal prophylaxis did not affect the incidence of IC [76]. Similar to Bartoletti, in a recent singlecenter study, Shaik et al showed that enteric-drained pancreas transplant recipients who did not receive systemic antifungal prophylaxis had similar infectious complications, including an incidence of invasive candidiasis of 3.6%, which is similar to previously reported rates [75].…”
Section: Pancreassupporting
confidence: 74%
“…The incidence of IC following pancreas transplantation ranges from 2.7% to 20% [1,[75][76][77][78][79]. There are no differences in the incidence of invasive candidiasis between different types of pancreas transplants (simultaneous pancreas-kidney, pancreas transplant alone, pancreas after kidney) [80].…”
Section: Pancreasmentioning
confidence: 99%
“…A selective policy of antifungal prophylaxis in patients at higher risk for invasive fungal infection is justified. Most centers use a protocolized short duration, systemic antifungal prophylaxis strategy 312,[314][315][316][317][318][319][320][321]. Experts recommended the use of antimycotic prophylaxis, as per center protocol, to mitigate the risk of invasive fungal infections.5.10.4 | Antimicrobial prophylaxisPancreas transplantation is associated with a high risk of bacterial infection.…”
mentioning
confidence: 99%
“…Initial empiric therapy recommended echinocandin, whereas fluconazole is an acceptable alternative in patients not critically ill and/or considered unlikely to have a fluconazole‐resistant Candida species 28 . These recommendations are also confirmed in the guidelines from the American Society of Transplantation Infectious Diseases Community of Practice, published in 2019 28 . Treatment of intra‐abdominal candidiasis should also include source control with appropriate drainage and/or debridement.…”
Section: Discussionmentioning
confidence: 96%
“…In 2016, the IDSA published guidelines to standardize the use of antifungal therapy in patients presenting clinical evidence of intra‐abdominal infection and high‐risk factors for candidiasis, including recent abdominal surgery, anastomotic leaks, or necrotizing pancreatitis 24 . Initial empiric therapy recommended echinocandin, whereas fluconazole is an acceptable alternative in patients not critically ill and/or considered unlikely to have a fluconazole‐resistant Candida species 28 . These recommendations are also confirmed in the guidelines from the American Society of Transplantation Infectious Diseases Community of Practice, published in 2019 28 .…”
Section: Discussionmentioning
confidence: 99%